Phosphorus resorption and tissue longevity of roots and leaves – importance for phosphorus use efficiency and ecosystem phosphorus cycles - Veneklaas, Erik J. (Plant and soil, 2022)
Plants recycle substantial amounts of phosphorus (P) from senescing tissues, reducing the need to take up P from soils. This paper reviews P recycling in plants, factors that determine its quantitative importance, and evidence that species from low-P ecosystems possess traits that enhance P recycling. It focuses on roots and leaves where most P turnover occurs. Knowledge of root traits and dynamics lags far behind that of leaves, but P concentrations, lifespans, resorption percentages and biomass allocation of roots are all comparable to those of leaves. Relationships among traits that influence P recycling appear more complex in roots than in leaves. Long root lifespans may not be adaptive in soils with very low P availability. At the plant level, the quantitative importance of P resorption to support P requirements decreases with net growth rate and with tissue longevity. Leaf lifespans are negatively correlated with growth rates and resource availability, but root lifespans may not be, indicating that further research into root dynamics and P resorption is essential to understand the role of roots in both P conservation and P acquisition.